2019
DOI: 10.2147/ott.s203724
|View full text |Cite|
|
Sign up to set email alerts
|

<p>HIF1α/PD-L1 axis mediates hypoxia-induced cell apoptosis and tumor progression in follicular thyroid carcinoma</p>

Abstract: Background Hypoxia-inducible factor 1α (HIF-1α) and programmed cell death-1 protein ligand 1 (PD-L1) are implicated in the metastasis and progression processes of multiple cancers. Hypoxia selectively elevates PD-L1 expression via HIF1α activation in several solid tumors; however, the regulatory effect of HIF1α on PD-L1 in the pathogenesis of follicular thyroid cancer (FTC) remains unclear. This study aims to investigate the regulatory effect of HIF1α on PD-L1 and their potential roles in FTC path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…Additionally, some cytokines have been shown to work synergistically to upregulate PD-L1 expression in tumors such as TNFα with IFNγ (166) and with IL-17 (162). Besides inflammatory cytokines extrinsically modulating PD-L1 expression, hypoxia in the tumor microenvironment selectively elevates PD-L1 expression via HIF-1α activation in melanoma, breast, lung, thyroid and prostate cancer (9, 146,167). In recent studies, HIF-2α has also been shown to correlate with PD-L1 expression in clear cell renal cell carcinoma (168,169).…”
Section: Extrinsic Factors Promote Pd-l1 Expressionmentioning
confidence: 99%
“…Additionally, some cytokines have been shown to work synergistically to upregulate PD-L1 expression in tumors such as TNFα with IFNγ (166) and with IL-17 (162). Besides inflammatory cytokines extrinsically modulating PD-L1 expression, hypoxia in the tumor microenvironment selectively elevates PD-L1 expression via HIF-1α activation in melanoma, breast, lung, thyroid and prostate cancer (9, 146,167). In recent studies, HIF-2α has also been shown to correlate with PD-L1 expression in clear cell renal cell carcinoma (168,169).…”
Section: Extrinsic Factors Promote Pd-l1 Expressionmentioning
confidence: 99%
“…Of clinical relevance, the overexpression of PD-L1 appears to predict worse prognosis, identifying patients at-risk of TC progression, representing real hope for the early management of advanced WDTC (18 clinical studies totaling 3107 patients, Table 3 ) 34 - 37 , 48 - 50 , 57 , 61 - 70 . Indeed, the expression of PD-L1 independently correlated with all clinicopathological markers of poor TC prognosis 5 : such as male gender, an age > 45 years 49 , 50 , 69 , tumor size (including extra-thyroid or multifocal lesions) 36 , 49 , 57 , 63 , 66 , 69 , lymphovascular invasion and lymph node metastasis 34 , 36 , 49 , 62 , 64 , 65 , 69 , 70 , or TNM stage 48 , 50 , 63 . Not surprisingly given its role in tumor immune escape, PD-L1 overexpression (protein and mRNA) is associated with reduced progression-free survival (PFS) in PTC patients 48 , 49 , 57 , 64 , 69 .…”
Section: The Pd-1/pd-l1 Axis In Thyroid Diseasesmentioning
confidence: 99%
“…A one-step TUNEL kit (Beyotime Institute of Biotechnology, Haimen, China) was used for TUNEL staining as previously described. 28 After the treatment, HepG2 cells were incubated with fluorescein-dUTP (Invitrogen; Thermo Fisher Scientific, Inc.) to stain apoptotic cell nuclei and DAPI (5mg/mL) to stain all cell nuclei at room temperature for 3 min. The slides were imaged under a confocal microscope at least 5 random separate fields.…”
Section: Tunel Mtt and Ldh Release Assaymentioning
confidence: 99%